Occupational Safety and Health Evaluation of Scaffolding Systems in Offshore Deck Areas - Doni Suseno; Khairul Khairul (Jurnal Ilmiah Teknik, 2026)
Offshore scaffolding activities involve high-risk work, especially in deck areas where workers operate at height and near emergency evacuation facilities. Improper scaffolding installation and use may cause structural hazards, workplace accidents, and disruption of liferaft systems. Objective: This study aims to analyze scaffolding implementation in offshore deck areas from the perspective of occupational safety and health. Method: A qualitative descriptive method was used through direct field observation and documentation at the Natuna Forel offshore platform. Data were analyzed by identifying scaffolding components, safety procedures, inspection practices, and potential hazards based on relevant OSH standards and scaffolding guidelines. Findings: The results show that scaffolding implementation generally complied with OSH requirements, particularly in terms of pipe connection, joint position, access system, guardrail installation, PPE use, and inspection procedures. However, a potential hazard was identified in scaffolding installed near the liferaft area, where several pipe ends were not equipped with protective plastic tube end caps. This condition may damage emergency evacuation equipment and reduce emergency response effectiveness. Implications: The findings suggest that offshore scaffolding safety assessment should not only focus on structural stability and worker access but also consider the interaction between temporary structures and emergency facilities. Originality: This study offers a specific contribution by highlighting scaffolding safety in offshore deck areas, particularly its potential impact on liferaft emergency systems, which is rarely discussed in onshore-focused scaffolding studies.